House Prices, Credit and the Effect of Monetary Policy in Norway: Evidence from Structural VAR Models - Ørjan Robstad (Norges Bank, 2014)
This paper investigates the responses of house prices and household credit to monetary policy shocks in Norway, using Bayesian structural VAR models. I find that the effect of a monetary policy shock on house prices is large, while the effect on household credit is muted. This is consistent with a relatively small refinancing rate of the mortgage stock each quarter. Using monetary policy to guard against - financial instability by mitigating property-price movements may prove effective, but trying to mitigate household credit may prove costly in terms of GDP and inflation variation.
hdl:11250/2495980
Keywords: E32; E37; E44; E52; 330; structural VAR; house prices; credit; monetary policy